SOCIETY’S PSYCHO-CULTURE AND ITS IMPACT UPON PERSONALITY’S DEVELOPMENT - Пономаренко, Я. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article describes features of the formation society’s psycho-culture and its influence on the personality.